Analysis of Determining Superior Products Micro, Small and Medium Enterprises (MSMEs) East Belitung Regency Using Combination of AHP and SMART Methods - Nurjanah, Siti; Rachim, Abdul; Haris Oktabian, Roy; Muharam, Harjum (International Journal of Educational Technology and Artificial Intelligence, 2024)
COVID-19 pandemic has affected economies globally and how these effects could potentially apply to a region like East Belitung. The determination of superior products for Micro, Small and Medium Enterprises (MSMEs) of East Belitung Regency aims to encourage the acceleration of the growth of economic businesses based on the potential of local resources in order to create jobs and increase community income. The determination of the leading product is carried out in two steps, namely through the Analytical Hierarchy Process (AHP) method to determine the weight of 12 criteria that have been determined by East Belitung Regency Regional Regulation Number 10 of 2021 and then determine the ranking of leading products using the Simple Multi Attribute Rating Technique (SMART) method. The resources used are the results of interviews and questionnaires distributed to parties who are experts in the development of MSMEs, both internal to the Regional Government and external to the MSME Development Group. The results showed that pepper products have the potential to become the flagship product of East Belitung Regency MSMEs so that it needs to be determined through a Regent Decree as mandated by the Regional Regulation.